Restitution of mistakenly transferred bitcoins - SEE, Alvin W. L. (Institutional Knowledge at Singapore Management University, 2022)
The first Malaysian judgment of precedential value relating to the recovery of mistakenly transferred cryptocurrency, Robert Ong Thien Cheng v LUNO Pte Ltd and BitX Malaysia Sdn Bhd, is uncharacteristically short but raises important issues in the law of unjust enrichment. Even within the Commonwealth, this is the fi rst reported case involving an unjust enrichment claim to recover mistakenly transferred cryptoassets.